Suspension sediment contribution from bioturbation in intertidal sites of SW Atlantic mesotidal estuary: data analysis and numerical modelling - Angeletti, Sabrina (2018)
The suspended sediment contribution arising from the bioturbation activity of Neohelice granulata at intertidal sites of the Bahía Blanca estuary was analysed using several approaches, ranging from field experiments to numerical modelling. Crabs from the mudflat remove, trap and erode more sediment from their burrows per unit area than those from saltmarshes, as a consequence of the high population density and the mobility of cohesive sediments. The results obtained through the MOHID simulations showed that the sediments that were bioavailable in the intertidal of Puerto Cuatreros were maintained in the water column much longer than sediments in Villa del Mar. This longer residence time in the area could be because of the geomorphological and hydrodynamic characteristics of the internal area of the estuary, where numerous tidal channels coexist and phenomena of “retention” occur before entry into the main channel. By contrast, in Villa del Mar, located in the middle of the estuary, the sediments are affected by a greater water depth and higher tidal current speeds. In addition, the waves caused by the winds can be a determining factor in the spatio-temporal evolution of the bioavailable sediment in the water column of the study areas.